2000
DOI: 10.1161/01.atv.20.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Platelet-Derived Growth Factor Receptor–Specific Tyrphostin Inhibits Neointimal Formation in Rats

Abstract: Abstract-Signal transduction through the platelet-derived growth factor (PDGF)/PDGF receptor (PDGFR) system is involved in the process of postangioplasty restenosis. Tyrphostins are low molecular weight inhibitors of protein tyrosine kinases. We assessed the antiproliferative effects of PDGFR␤-specific tyrphostin AG-1295 in vitro and in vivo. AG-1295 significantly inhibited rat smooth muscle cell growth stimulated by PDGF-BB or FCS. This antiproliferative effect was paralleled by reversible reduction of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 51 publications
1
36
1
Order By: Relevance
“…The section with the greatest luminal narrowing by neointima was analyzed as previously described (49). The residual lumen, the area bounded by the internal elastic lamina (original lumen), and the area circumscribed by the external elastic lamina (total arterial area) were measured directly.…”
Section: Morphometric Analysismentioning
confidence: 99%
“…The section with the greatest luminal narrowing by neointima was analyzed as previously described (49). The residual lumen, the area bounded by the internal elastic lamina (original lumen), and the area circumscribed by the external elastic lamina (total arterial area) were measured directly.…”
Section: Morphometric Analysismentioning
confidence: 99%
“…In vitro experiments have shown that the tyrphostin AGL-2043, as well as the related tyrphostin AG-1295, selectively inhibit PDGF receptors and selectively inhibit SMC proliferation in culture (163). Local delivery of AG-1295 by a perivascular polymeric matrix or intraluminally with nanoparticules inhibited intimal hyperplasia in a rat carotid injury model (164,165). AGL-2043 DESs with a biodegradable, polymeric coating (162) led to a reduction of in-stent neointima formation in a pig coronary injury model.…”
Section: Perlecanmentioning
confidence: 99%
“…Rat smooth muscle cells (SMCs) were isolated and cultured from thoracic aortas of either Sabra male rats or Sprague-Dawley female rats weighing 200-300 g by the explant method. 12 Freshly dissected blood vessels from animals killed less than 5 min previously were placed in cold media. The vessels were aseptically cleaned by removing the fat and connective tissue (adventitia) and were cut longitudinally.…”
Section: Cells Culture Studiesmentioning
confidence: 99%
“…10,36 The procedures were adapted 12,13,28 with some modifications and adjustment for antisense delivery. Animals were obtained from Harlan Laboratories, Israel, and housed in the animal facilities of the Faculty of Medicine, The Hebrew University of Jerusalem, conforming to the standards for care and use of laboratory animals of The Hebrew University of Jerusalem and NIH.…”
Section: Inhibition Of Neointimal Formation -Rat Injured Carotid Modelmentioning
confidence: 99%
See 1 more Smart Citation